2014
DOI: 10.1108/tqm-12-2010-0041
|View full text |Cite
|
Sign up to set email alerts
|

Why TQM programmes fail? A pathology approach

Abstract: Purpose-Implementing total quality management (TQM) is not without difficulties and achieving its promised benefits is not easy. The purpose of this paper is to identify the barriers to TQM successful implementation. Design/methodology/approach-A literature review has been done to explore the major reasons for the failure of TQM programmes. Findings-An examination of 54 TQM empirical studies identified 54 obstacles to successful TQM implementation. There are both theoretical and practical difficulties in apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 103 publications
1
101
1
10
Order By: Relevance
“…It is very difficult to sustain the benefits of a quality management system in Iranian healthcare organisations while they are suffering from these organisational diseases. Managers and policy-makers must invest in the following five capitals (see Figure 2) to overcome the above-mentioned obstacles and facilitate the implementation of quality management (52). Physical capital refers to any non-human asset used in the production of products and services.…”
Section: Discussionmentioning
confidence: 99%
“…It is very difficult to sustain the benefits of a quality management system in Iranian healthcare organisations while they are suffering from these organisational diseases. Managers and policy-makers must invest in the following five capitals (see Figure 2) to overcome the above-mentioned obstacles and facilitate the implementation of quality management (52). Physical capital refers to any non-human asset used in the production of products and services.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some authors (Babatunde and Low, 2015) have adopted the terms positive and negative conflicts to underscore the potential impact of a conflict on perceived quality performance of a foreign party by its host as presented in Figure 2. Effective TQM implementation interacts with national culture in a bi-directional or culture-specific relationship (Noronha, 2003;Sousa-Poza et al, 2001) in order to prevent implementation failure (Green, 2012;Mosadeghrad, 2014). Studies have found the Chinese cultural values' impacting on their TQM implementation (Noronha, 2002) and affecting the perception of their project performance overseas (Ulluh Khan, 2014).…”
Section: 2mentioning
confidence: 99%
“…This progression further led to the emanation of TQM. Although TQM triggered the human community to apply numerous tools and techniques to achieve continuous quality improvement, their impact on achieving business results was not very impressive [20]. In order to tune the TQM to meet the needs of achieving business results, Six Sigma was developed by Bill Smith in Motorola in the year 1987 [14].…”
Section: History and Growth Of Six Sigmamentioning
confidence: 99%
“…Many other tools like F test, Enterprises Resource Planning, CTQ tree and histogram have appeared in only one paper reporting the application of DMAIC phases while executing Six Sigma projects. He et al [47] Human resource Management 16 Kumaravadivel and Natarajan [31] Manufacturing 17 Banawi and Bilec [7] Construction process 18 Jirasukprasert et al [21] Manufacturing 19 Kumar et al [48] Online retailing business 20 Kumar et al [49] Financial services 21 Southard et al [50] Hospital management Amidst the usage of these techniques and tools, it is interesting to note the gradual increase of the frequency of appearance of Poka-Yoke in the Six Sigma literature arena. As mentioned earlier, Poka-Yoke system has the power to prevent the occurrence of failures [52] and enable organisations to produce products and offer services within Six Sigma limit of 3.4 DPMO [42].…”
Section: Tools and Techniques Used In Six Sigmamentioning
confidence: 99%